2022
DOI: 10.1002/ejic.202100884
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic and Mesoionic Carbenes of Manganese and Rhenium in Catalysis

Abstract: The use of N‐heterocyclic carbenes (NHCs) in manganese and rhenium catalysis is underdeveloped in comparison to other transition metals. Herein, we cover the recent and stimulating progress in homogeneous catalysis using Mn‐NHC complexes, namely in hydrosilylation, hydrogenation, and borrowing hydrogen processes. Of particular interest is the application of Mn and Re NHC catalysts in the electrochemical and photochemical reduction of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
(211 reference statements)
0
21
0
Order By: Relevance
“…Over the last few decades, metal complexes bearing N-heterocyclic carbene (NHC) ligands have proved to be a worthy substitute for expensive phosphine-based complexes for catalyzing several C–C, C–N, and C–O coupling and hydrogen transfer reactions . Earlier, chelating bis-NHC complexes of 4d and 5d transition metals have shown significant catalytic activity toward several hydrogen transfer reactions. − , With the advancement in 3d-metal catalysis, bis-NHC-Mn­(I) complexes have recently been proven immensely useful for catalyzing various alcohol dehydrogenative coupling reactions . Seminal works by the Ke group who reported a methyl wingtip containing chelating bis-NHC-Mn­(I) complex for the N-alkylation of anilines with alcohols and the synthesis of α-alkylated ketones and quinolines following the alcohol dehydrogenative coupling strategy are noteworthy. , In 2020, they reported a bis-carbene-(CNC)­Mn­(I) complex for the acceptor-less dehydrogenative coupling between primary and secondary alcohols to the corresponding ketones .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, metal complexes bearing N-heterocyclic carbene (NHC) ligands have proved to be a worthy substitute for expensive phosphine-based complexes for catalyzing several C–C, C–N, and C–O coupling and hydrogen transfer reactions . Earlier, chelating bis-NHC complexes of 4d and 5d transition metals have shown significant catalytic activity toward several hydrogen transfer reactions. − , With the advancement in 3d-metal catalysis, bis-NHC-Mn­(I) complexes have recently been proven immensely useful for catalyzing various alcohol dehydrogenative coupling reactions . Seminal works by the Ke group who reported a methyl wingtip containing chelating bis-NHC-Mn­(I) complex for the N-alkylation of anilines with alcohols and the synthesis of α-alkylated ketones and quinolines following the alcohol dehydrogenative coupling strategy are noteworthy. , In 2020, they reported a bis-carbene-(CNC)­Mn­(I) complex for the acceptor-less dehydrogenative coupling between primary and secondary alcohols to the corresponding ketones .…”
Section: Introductionmentioning
confidence: 99%
“…38 Despite these interesting features, the chemistry and catalysis of Mn with MICs have remained elusive. 35,36 In this work, we report the synthesis and characterization of a new family of tricarbonyl Mn(I) complexes bearing bis(1,2,3triazol-5-ylidene) ligands and their catalytic performance in the N-alkylation of anilines with alcohols. In addition, related Re(I) triazolylidene complexes have been prepared and applied in this catalytic process to compare the activity of Mn and Re complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Later, other authors showed the capability of this complex to efficiently catalyze the N-alkylation of anilines with alcohols, the α-alkylation of ketones with alcohols, and, more recently, the transformation of α,β-unsaturated ketones to α-methylated ketones using methanol . Apart from classical imidazolium-derived NHCs, we are also interested in the chemistry of manganese with mesoionic carbenes (MICs). MICs, especially those derived from 1,2,3-triazolylidenes, make up an interesting subclass of NHCs that have advanced to become a prominent class of ligands in catalysis. In many cases, their strong σ-donor and weak π-acceptor properties yield metal complexes with enhanced catalytic activities and stability . Despite these interesting features, the chemistry and catalysis of Mn with MICs have remained elusive. , …”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, NHC-transition metal complexes (NHC = N-Heterocyclic Carbene) have attracted significant attention not only for uses in organometallic chemistry and catalysis but also as bio-organometallics, notably due to the high stability of the NHC-metal bonds under physiological conditions. …”
Section: Introductionmentioning
confidence: 99%